Soft, Erythematous Nodule of the Ankle with a String of Pearls Vascular Pattern: A Quiz - Emanuele Cozzani; Astrid Herzum; Roberto Russo; Claudia Micalizzi; Giulia Scaglione; Francesco Cabiddu; Aurora Parodi (Medical Journals Sweden, 2020)
Abstract is missing (Quiz)